Amp 1q21 is more predictable with dismal survival than gain 1q21 of newly diagnosed multiple myeloma in real‐world analysis. Issue 7 (30th March 2022) - Wang, Yu‐tong; Bao, Li; Chu, Bin; Chen, Xiao‐huan; Lu, Min‐qiu; Shi, Lei; Gao, Shan; Fang, Li‐juan; Xiang, Qiu‐qing; Ding, Yue‐hua
Abstract: Introduction: The gain/amplification (amp) of 1q21 is one of the most common high‐risk chromosome abnormality (HRCA) in multiple myeloma (MM). The prognostic value of 1q21+ remains to be controversial on the status of gain or amp and the combination of other HRCAs. Methods: In this retrospective study, we included 318 newly diagnosed MM (NDMM) patients who had fluorescence in situ hybridization (FISH) data and treated with novel agents in our department. Results: Our study noted MM patients with amp 1q21 were more likely accompanied with t(4;14), t(14;16), and t(14;20). Patients with amp 1q21 presented with elder age, advanced Revised International Staging System (R‐ISS) stages, anemia, and more plasma cells in bone marrow compared to patients with gain 1q21 alone and no 1q21+. Moreover, amp 1q21 alone correlated with shorter progression‐free survival (PFS) (22.8m vs. 40.5m vs. 39.6m) and overall survival (OS) (45.2m vs. NA vs. 83.5m) compared with gain 1q21 alone and no FISH abnormalities. Although the high ratio of proteasome inhibitor and immunomodulatory drugs used in patients with amp 1q21, the overall response (ORR) was the lowest compared with no 1q21+ and gain 1q21. Multivariate analysis defined amp 1q21 as an independent prognostic marker for NDMM patients, rather than gain 1q21. Conclusion: The amp 1q21 predict inferior treatment response and survival, especially coexisted with high‐risk IgH translocation. Abstract : The prognostic value of 1q21+ detected by FISH remains to be controversial on the status of gain or amp for multiple myeloma (MM). The real‐world data demonstrated MM patients with amp 1q21 more likely combined with other high‐risk chromosome abnormality. Meanwhile, the individualism of amp 1q21 correlated with poor treatment response and survival.